Acquisition of the ownership of agricultural lands in Hungary, taking the EU’s and other countries’ law into consideration - Szilágyi, János Ede (Zbornik radova Pravnog fakulteta u Novom Sadu, 2017)
The present article concentrates on the acquisition of ownership (and in some respects: use) of agricultural and forestry lands, especially as to the cross-border aspects. One of the hypotheses of the article is that the above mentioned issue is a topical question almost all around the world. Nevertheless, the article focuses on a European aspect of the cross-border acquisition, namely the new land law rules of the EU’s Member States having joined the European Union in 2004 and 2007. In 2014 and 2015, the European Commission had assessed the land law of these Member States (i.e. Bulgaria, Hungary, Latvia, Lithuania, Slovakia) and initiated infringement procedures against these countries at the Court of Justice of the European Union. Besides the regulation of these new Member States of the EU, the present article deals with the legislation of other Member States as well as the provisions of non-EU states. The article gives substantial consideration to phenomena such as sovereignty, land-hunger or soil degradation which may exercise significant influence on the land law of a state.